The effect of prophylactic negative pressure wound therapy on infection in obese women after C-section: a meta-analysis - Aris Widiyanto; Santy Irene Putri; Asruria Sani Fajriah; Yuly Peristiowati; Agusta Dian Ellina; Joko Triatmojo (Universitas Gadjah Mada, 2023)
Most caesarean wounds resulted in infection. This become a huge burden on the health care system, considering the high number of women undergoing this type of surgery. Negative pressure wound therapy (NPWT) has been recommended for a wide variety of lesions including open abdominal wounds. The purpose of this study was to investigate the effect of prophylactic NPWT on infection in obese women after a C-section. This was a systematic review and meta-analysis study that used articles from online databases of EBSCO, Google Scholar, and PubMed which published until 2022. The dependent variable was infections post C-section, while the independent were NPWT and standard wound therapy. The data was analyzed by RevMan 5.3. This study showed that there is no difference in the outcome of superficial site infection (SSI), deep site infection (DSI), wound dehiscence, seroma, and hematoma between women with obesity after caesarean delivery who used NPWT and standard dressing.